Rekonstruksi Makna Larangan Memakan Harta Secara Batil dalam Al-Qur’ān melalui Hermeneutika Double Movement Fazlur Rahman: Reconstructing the Meaning of the Prohibition Against Unjustly Acquiring Wealth in the Qur'an through Fazlur Rahman's "Double Movement" Hermeneutics - sulkifli sulkifli; Adliansyah; Baharuddin Akmal; Nasra Yunita (QISTHOSIA : Jurnal Syariah dan Hukum, 2026)
This article examines the prohibition of consuming wealth unlawfully (akl al-amwal bi al-batil) in the Qurʼan through Fazlur Rahman’s double movement hermeneutical approach. The study is based on the observation that interpretations of Qurʼanic verses concerning unlawful acquisition of wealth are often confined to normative and textual understandings, making them less capable of addressing the complexities of contemporary economic issues. This research employs a library-based qualitative method and adopts a contemporary Qurʼanic interpretation perspective by analyzing both the historical context of revelation and its relevance to present-day social realities. The discussion focuses on Q.S. al-Nisā’ (4):29 and Q.S. al-Baqarah (2):188 as the primary textual foundations for the prohibition of acquiring wealth through illegitimate means. The findings reveal that the prohibition of consuming wealth unlawfully is not merely a legal-formal injunction but also embodies universal moral principles, including justice in the acquisition and management of wealth, mutual consent in transactions, transparency, and the protection of human dignity and welfare. Through the first movement of Rahman's hermeneutics, the study finds that these verses were revealed as a response to exploitative and unjust economic practices prevalent in pre-Islamic Arabian society. The second movement demonstrates that the moral ideals embedded in these verses remain relevant for evaluating contemporary economic practices, such as digital fraud, corruption, market manipulation, online gambling, and other forms of economic exploitation. Therefore, the double movement approach highlights the dynamic and contextual nature of Qurʼanic teachings, demonstrating their continued relevance in addressing modern socio-economic and transactional challenges.